FORMULASI KRIM EKSTRAK BIJI KUPA (Syzygium polycephalum) DAN PENENTUAN NILAI SPF (Sun Protection Factor) SECARA IN VITRO - Wulan Novian Dewi; Ira Rahmiyani; Anindita Tri Kusuma Pratita; Resha Resmawati Shaleha (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
The high intensity of ultraviolet rays and exposure to the sun too often can have harmful effects on the skin, so sunscreen can be used to prevent interference from UV rays. The purpose of this study was to determine the activity of sunscreen and determine the SPF value of the extract and cream preparation of Kupa (Syzygium polycephalum) seeds. In this study, the seeds of Kupa fruit were extracted by the graded maceration method using 96% ethanol, ethyl acetate, and n-hexane as solvents. The ethyl acetate extract was formulated in the form of a cream dosage form with the added concentration of Kupa seed extract, namely 0.1% (F1), 0.2% (F2), and 0.5% (F3). Furthermore, the determination of the value of sunscreen on the extract and cream preparation using UV-Vis spectrophotometry and evaluation of the physical properties of the cream preparation include organoleptic tests, homogeneity, pH tests, spreadability, adhesion, and viscosity. The results showed that the SPF values ??of ethanol, ethyl acetate, and n-hexane extracts at a concentration of 200 ppm were 14.29; 19.32, and 14.02. While the SPF value of ethyl acetate extract cream preparations of Kupa fruit seeds F1, F2, and F3 respectively was 1.97; 2.96, and 4.96. Kupa seed extract has activity as a sunscreen with maximum and ultra protection levels. While the preparation of 0.5% ethyl acetate extract of Kupa seed had sunscreen activity with moderate protection. The physical properties of the cream preparations gave good results during the test.